Development of a Causal Relationship Model with Learning Responsibilities of Matthayomsueksa 5 Students under the Secondary Education Service Area Office 20 - ภูยาทิพย์ จรินทิพย์; ศรีสะอาด บุญชม (Journal of Roi Et Rajabhat University, 2016)
This study aimed to 1) identify the causal relations between the variables influencing learning responsibilities of Matthayomsueksa 5 (grade 11) students under the Secondary Education Service Area Office 20, and 2) examine the goodness of fit of the model developed of the cause relationships among the variable influencing learning responsibilities of the sample. The sample used in this study consisted of 460 Matthayomsueksa 5 students in the second semester of the academic year 2015 using the multi–stage random sampling technique. The instruments used in the study were 5–rating–scale inventories. They included a 20–item test on learning responsibilities, a 20–item test on future orientation characteristics, a 30–item test on self– concept, a 20–item test on achievement motive and a 20–item test on attitude toward studying, with discriminating powers ranged (rxy) from .205 to .543, .283 to .728, .212 to .698, .235 to .702 and .232 to .741 respectively and reliabilities () of 0.733, 0.897, 0.839, 0.894 and 0.898 respectively. Data analyses employed were descriptive statistics, Confirmatory Factor Analysis (CFA Structural Equation Model (SEM) using Mplus 7 computer program. The result of study were as follows : The development and goodness of fit test result of a causal relationship model with learning revealed that the model was consistent with the empirical data at a high level tested by the index statistic test of the consistency = 80.612, df = 66, /df = 1.22, P–Value = 0.1065, CFI = 0.996, TLI = 0.993, RMSEA = 0.022 and SRMR = 0.046. The variance with the highest direct influencing on the learning responsibilities was latent variance of self–concept (SEL), latent variance of attitude toward studying (ATT), latent variance of achievement motive (MOT) and latent variance of future orientation characteristics (FUO) respectively. It was revealed that the model co– factor explained the variance of the learning responsibilities at 63.9 percent.